Coleções de fé, fluxos materiais e hibridismos nas festas religiosas = Collections of faith, material flows and hybrids at religious festivals - Lopes, José Rogério (Ciencias sociales y religión, 2014)
Religious festivals have undergone important contemporary changes since the modernization of their devotional models, processes of organization of rituals, to the processes of cultural patrimony thereof. From ethnographic reports of three religious festivals surveyed by the author in Brazil is intended to expose how these transformations enlarge the scope for the participation of different social actors -marketing agents, audiovisual production in culture, among others -in the religious. Phenomenon. In this broadened scope, agencies such actors circulate regarding the local material culture generally appropriate private collections of devotees and other local subjects, superimposed onthe dynamics of ritual feasts that produce hybridity in the festive landscapes.